WEB-BASED BUSINESS DATA COLLECTION APPLICATION IMPLEMENTATION OF UMKM PROCESS - Irwan; Nurul Hamdi (INFOKUM, 2022)
Micro, Small and Medium Enterprises (UMKM) in Kelambir Lima Kebon, Deli Serdang Regency, are currently growing rapidly. Many groups of actors in it can also create huge job opportunities in the surrounding environment, so that it is very helpful for the unemployed. In empowering UMKM in this Technology era, one of them is through a website-based UMKM communication center. Its function is to build digitalized media such as websites so that all information related to the development of UMKM in Kelamibr Lima Kebon, Deli Serdang Regency, can also expand its business network. The method used to design the web used is use case diagrams and activity diagrams, for research objects that are actively running their business in kelambir lima kebon. The web that will be produced later is very interactive, this is because the resulting communication runs in two directions between customers and UMKM so that it can build a customer community that can generate an intention to buy products marketed via the Web.